Multi-strain Probiotics Upregulated Anti-inflammatory Properties and Reduced Pasteurella multocida Mortality in Broilers. (March 2022) - Reuben, R.; Sarkar, S.; Ibnat, H.; Setu, M.A. Ahasan; Roy, P.; Jahid, I.
Abstract : Purpose: Pasteurella multocida is the highly contagious and zoonotic pathogen of a broad range of animal diseases causing devastating ecological and economic challenges globally. While about 80.5% of P. multocida infections have shown high degree of resistance to broad range of commonly used antibiotics, dietary inclusion of probiotics may become a suitable alternative in mitigating P. multocida infections in animals, hence reducing human spread as well as safeguarding the environment. It was hypothesized that dietary supplementation with multi-strain probiotics consisting of Lactobacillus plantarum, L. fermentum, Pediococcus acidilactici, Enterococcus faecium and Saccharomyces cerevisiae would mitigate P. multocida infection in broilers as well as improving gut health, haemato-biochemical parameters and growth performance. Methods & Materials: A total of 120 birds were randomly allocated to 6 treatments with 2 replicates each, and were fed with a basal diet supplemented with multi-strain probiotics (10 8 CFU/kg) and then orally challenged with 10 8 CFU/mL of P. multocida . Clinical manifestations of P. multocida infection and mortality were recorded as well as the expression of anti-inflammatory genes, haemato-biochemical parameters, gut microbiota and growth performance. Results: Probiotics supplementation significantly (P < 0.05) improved growth performance and feed efficiency as well as reducing (P < 0.05) the population of intestinal P. multocida, enterobacteria, and mortality. Haemato-biochemical parameters including total cholesterol, white blood cells (WBC), proteins, glucose, packed cell volume (PCV) and lymphocytes improved (P < 0.05) among probiotics fed birds when compared with the controls. Also, transcriptional profiles of anti-inflammatory genes including hypoxia inducible factor 1 alpha (HIF1A), tumor necrosis factor- (TNF) stimulated gene-6 (TSG-6) and prostaglandin E receptor 2 (PTGER2) in the intestinal mucosa were upregulated (P < 0.05) in probiotics fed birds. Conclusion: The dietary inclusion of the multi-strain probiotics improves growth performance, feed efficiency and intestinal health while attenuating inflammatory reaction, clinical signs and mortality associated with P. multocida infection in broilers, and these suggest that the probiotics can be used as alternative against P. multocida infections.